Qualitative evaluation of enabling factors and barriers to the success and sustainability of national public health institutes in Cambodia, Colombia, Liberia, Mozambique, Nigeria, Rwanda and Zambia. Issue 4 (1st April 2022) - Woldetsadik, Mahlet A; Bratton, Shelly; Fitzpatrick, Kaitlin; Ravat, Fatima; Del Castillo, Lisetta; McIntosh, Kelsy J; Jarvis, Dennis; Carnevale, Caroline R; Cassell, Cynthia H; Chhea, Chhorvann; Prieto Alvarado, Franklyn; MaCauley, Jane; et al.
Abstract : Objectives: The success of National Public Health Institutes (NPHIs) in low-income and middle-income countries (LMICs) is critical to countries' ability to deliver public health services to their populations and effectively respond to public health emergencies. However, empirical data are limited on factors that promote or are barriers to the sustainability of NPHIs. This evaluation explored stakeholders' perceptions about enabling factors and barriers to the success and sustainability of NPHIs in seven countries where the U.S. Centers for Disease Control and Prevention (CDC) has supported NPHI development and strengthening. Design: Qualitative study. Setting: Cambodia, Colombia, Liberia, Mozambique, Nigeria, Rwanda and Zambia. Participants: NPHI staff, non-NPHI government staff, and non-governmental and international organisation staff. Methods: We conducted semistructured, in-person interviews at a location chosen by the participants in the seven countries. We analysed data using a directed content analysis approach. Results: We interviewed 43 NPHI staff, 29 non-NPHI government staff and 24 staff from non-governmental and international organisations. Participants identified five enabling factors critical to the success and sustainability of NPHIs: (1) strong leadership, (2) financial autonomy, (3) political commitment and country ownership, (4) strengthening capacity of NPHI staff and (5) forming strategic partnerships. Three themes emerged related to major barriers or threats to the sustainability of NPHIs: (1) reliance on partner funding to maintain key activities, (2) changes in NPHI leadership and (3) staff attrition and turnover. Conclusions: Our findings contribute to the scant literature on sustainability of NPHIs in LMICs by identifying essential components of sustainability and types of support needed from various stakeholders. Integrating these components into each step of NPHI development and ensuring sufficient support will be critical to strengthening public health systems and safeguarding their continuity. Our findings offer potential approaches for country leadership to direct efforts to strengthen and sustain NPHIs.